Edukasi Tumbuh Kembang Pada Bayi Dan Balita Di Rt 25 Kelurahan Sawah Lebar Kecamatan Ratu Agung Kota Bengkulu - Oktavia, Friska; Angelia, Chery; Haryanti, Zulmi; Apriyanti, Delta; Renita, Renita (Jurnal Pengabdian Mitra Persada, 2024)
Real Work Lecture (KKN) activities are a form of community service carried out by students in an interdisciplinary, institutional and partnership manner as a form of higher education tridharma activities. With KKN, what has been received during lectures can be applied directly to the community. With this KKN, it is hoped that it can increase the attitude of independence and teamwork for students. KKN activities can complement students' self-empowerment towards professional competence. With KKN activities, it is hoped that students will be able to serve themselves in the community using the knowledge gained from lectures.Real Work Lectures (KKN) are held for students taking health education to provide experience to students, especially in the community environment, and it cannot be ruled out that every student implementing KKN should be able to maintain polite behavior and cultural etiquette and position themselves correctly towards every citizen/ KKN location community in order to train and develop student competencies.